A computer-aided approach to compare the production economics of fed-batch and perfusion culture under uncertainty - Lim, Ai Chye; Washbrook, John; Titchener-Hooker, Nigel John; Farid, Suzanne S. (Biotechnology and bioengineering, 2006)
Fed‐batch and perfusion culture dominate mammalian cell culture production processes. In this paper, a decision‐support tool was employed to evaluate the economic feasibility of both culture modes via a case study based upon the large‐scale production of monoclonal antibodies. The trade‐offs between the relative simplicity but higher start‐up costs of fed‐batch processes and the high productivity but higher chances of equipment failure of perfusion processes were analysed. Deterministic analysis showed that whilst there was an insignificant difference (3%) between the cost of goods per gram (COG/g) values, the perfusion option benefited from a 42% reduction in capital investment and a 12% higher projected net present value (NPV). When Monte Carlo simulations were used to account for uncertainties in titre and yield, as well as the risks of contamination and filter fouling, the frequency distributions for the output metrics revealed that neither process route offered the best of both NPV or product output. A product output criterion was formulated and the options that met the criterion were compared based on their reward/risk ratio. The perfusion option was no longer feasible as it failed to meet the product output criterion and the fed‐batch option had a 100% higher reward/risk ratio. The tool indicated that in this particular case, the probabilities of contamination and fouling in the perfusion option need to be reduced from 10% to 3% for this option to have the higher reward/risk ratio. The case study highlighted the limitations of relying on deterministic analysis alone. © 2005 Wiley Periodicals, Inc.